Evidence of Recent Genomic Evolution in Gonococcal Strains With Decreased Susceptibility to Cephalosporins or Azithromycin in the United States, 2014–2016. (21st February 2019) - Thomas, Jesse C; Seby, Sandra; Abrams, A Jeanine; Cartee, Jack; Lucking, Sean; Vidyaprakash, Eshaw; Schmerer, Matthew; Pham, Cau D; Hong, Jaeyoung; Torrone, Elizabeth; Cyr, Sancta St; Shafer, William M; et al.
Abstract: Background: Given the lack of new antimicrobials or a vaccine, understanding the evolutionary dynamics of Neisseria gonorrhoeae is a significant public and global health priority. We investigated the emergence and spread of gonococcal strains with decreased susceptibility to cephalosporins and azithromycin using detailed genomic analyses of gonococcal isolates collected in the United States, 2014–2016. Methods: We sequenced genomes of 649 isolates collected through the Gonococcal Isolate Surveillance Project. We examined the genetic relatedness of isolates and assessed associations between clades and various genotypic and phenotypic combinations. Results: We identified a large and clonal lineage of strains (MLST ST9363) associated with elevated azithromycin minimum inhibitory concentration (AZI em ), characterized by a mosaic mtr locus (C substitution in the mtrR promoter, mosaic mtrR and mtrD) . Mutations in 23S rRNA were sporadically distributed among AZI em strains. Another clonal group (MLST ST1901) possessed 7 unique PBP2 patterns, and it shared common mutations in other genes associated with cephalosporin resistance. Conclusions: Whole-genome sequencing methods can enhance monitoring of antimicrobial resistant gonococcal strains by identifying gonococcal populations containing mutations of concern. These methods could inform the development of point-of-care diagnostic tests designed to determine the specific antibiotic susceptibility profile of a gonococcal infection in a patient. Abstract : Whole-genome sequencing reveals evidence of recent genomic evolution of gonococcal strains collected in the United States from 2014 to 2016, directly following CDC's 2012 change in treatment guidelines.